2011
DOI: 10.1134/s1995078011030074
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of mass-produced nanostructured titanium

Abstract: The structure and mechanical properties of nanostructured titanium VT1-0 derived using an ingenious method which combines helical and longitudinal rolling are studied in comparison with the properties of commercial titanium alloys VT6 and VT16, as well as VT1-0 in a coarse-grained stateye

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Previous low-cycle and high-cycle fatigue tests have shown that submicrocrystalline and nanostructured alloy VT1-0 shows fatigue resistance comparable to that of doped alloy VT6 [3,36]. Recent experiments have shown that pure SMC titanium, including in notched samples, has rather high fatigue resistance [61]. The available data give all grounds to consider nanostructured titanium VT1-0 quite suitable to replace domestic alloys VT6 and VT16, and also foreign alloy Grade-4 applied in stomatology.…”
Section: Application Of Nanostructured Titanium In Medicinementioning
confidence: 93%
See 3 more Smart Citations
“…Previous low-cycle and high-cycle fatigue tests have shown that submicrocrystalline and nanostructured alloy VT1-0 shows fatigue resistance comparable to that of doped alloy VT6 [3,36]. Recent experiments have shown that pure SMC titanium, including in notched samples, has rather high fatigue resistance [61]. The available data give all grounds to consider nanostructured titanium VT1-0 quite suitable to replace domestic alloys VT6 and VT16, and also foreign alloy Grade-4 applied in stomatology.…”
Section: Application Of Nanostructured Titanium In Medicinementioning
confidence: 93%
“…The most interesting results have been obtained in torsional tests of screw implants intended for osteosynthesis. According to the test results, the screws made of NS alloy VT1-0 are highly competitive in strength with those made of alloy VT16 [36,61] and also show extremely high plasticity (the maximum angle before torsional fracture is almost three times greater than that for alloy VT16). The structural plasticity of NS titanium is the most important reliability characteristic of screws made of this material, as under the conditions of actual medical prosthetic operation, fracture of screws made of a conventional titanium alloy may occur immediately in mounting.…”
Section: Application Of Nanostructured Titanium In Medicinementioning
confidence: 97%
See 2 more Smart Citations
“…Special features of plastic torsion strain of cylindri cal samples of nanostructural technically pure VT1 0 titanium (produced by combination of longitudinal and transverse screw rolling [1]; elemental content is shown in the table) at room temperature and the effect of severe plastic strain that has propagated as a local ized shear band through a sample are studied in the present work. The microstructure of the alloy studied in detail in [1,2] is a grain-subgrain mixture charac terized by an average size of the microstructural ele ments of about 220 nm with a nonequilibrium coeffi cient (the ratio between grain width and length mea sured on a plane cross section) of about 0.35.…”
mentioning
confidence: 99%